Building performance - al khafajy, Ali Mehsin; Hussain, Asma mohammed; Abood, Audaay Abbas (Iraqi Journal of Architecture and Planning, 2018)
The performance concept expressed as the distance between what is needed and what is realized, and a solution to the problem of evaluating the suitability of the product for the application, which in turn is an important factor from which to evaluate the building and therefore the identification and development paths of practice and professional experience in the housing field . the performance concept adopted after the need dictated by the new circumstances in the construction field as a result of the emergence of new concepts aim was to move away from compliance to traditional construction systems and the transfer rate from site to the factory .an experience of prefabrication can be solution to a growing problem of housing reliance on the mass production and the provision at the time of implementation as well as the economy and resources, these process of manufacturing - often - at the expense of performance dimension for the user and his need to shelter . Through a review of performance studies and prefabricated structural systems studies. the research pointed :â€ the absence of a clear vision of the performance concept and its impacts on residential buildings prefabricated and the absence of mechanism for evaluate it â€œ to be the research problem . The aim of the research is determined to : â€œ provide a vision of the performance concept and its impacts on residential buildings prefabricated and re-evaluation of these buildings in accordance with the performance concept â€œ. To achieve his aim , the research separate the procedural theory aspects of the operational aspects without losing sight of the integration of both theoretical and practical dimension to the performance concept . In this context, research split into two ; the first terms definition the performance concept and related aspects and its dimensions up to the extraction a conceptual framework for the basic concept The second terms addressed the field study the adoption of Al-Salam neighborhood in Baghdad as a case study and research was (50) random sample of residents of this district to evaluate the residential buildings performance, which made it possible to visualize residential complex performance (under study) in general .